Perception of staff in Qassim Medical College about Faculty development activities - A/Rahman, AlMohaimeed (International Journal of Health Sciences, 2011)
Objective: To explore the faculty member’s perceptions and attitudes regarding the faculty development activities. Research Design and Methods: An online survey that included all staff at the College of Medicine, Qassim University was done. Data were collected about the academic position, age, gender, academic phase, and the duration of employment at the college; the questions related to the faculty development activities included the level of participation and perceptions about quality and usefulness of these activities were answered. Results: The response rate was 68% (75 out of 110), More than half (56%) of respondents had attended the faculty development activities regularly. For the rest, the reasons for not attending regularly were other commitments (47%) and unsuitable timing of activities (53%); 60 % of respondents thought that attending the faculty development activities should be part of the faculty’s evaluation criteria. The most favored topics of the faculty development seminars were medical education and research. However, new faculty members had unfavorable comments about the medical education seminars. A majority of respondents preferred workshops as a method of learning. Finally, 91% of respondents thought that the content of the sessions should be posted on the College website. Conclusion: The medical education and research topics are the most favored by the faculties. Workshops are the most preferred method of learning. Newcomers are less satisfied with the medical education seminars. Keywords: faculty development, Saudi Arabia.